KEPRIBADIAN TOKOH DALAM CERPEN ANAK ‘UMĀRAH DENGAN PENDEKATAN PSIKOLOGI JUNG - Nurul Fadhilah, Eva Farhah (Arabic Literature Department, 2015)
This research reveals the aspects of personality of the characters contained in the children‟s short story entitled, 'Umārah. The theory used in this research is Jung's psychology of personality, while the method is qualitative descriptive. According to Jung's theory, the personality concept is totally psychia events, whether consciously or unconsciously. The research concludes that the personalities of characters are tasterintrovert, thinker-introvert, taster-extrovert, thinker-extrovert.